2009
DOI: 10.1002/vnl.20208
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of the efficiency of a series of commercial antioxidants studied by kinetic modeling in a liquid phase and during the melt processing of different polyethylenes

Abstract: reaction of cumene-initiated oxidation has demonstrated excellent applicability as an effective tool for preliminary quantitative assessment of antioxidant radical-scavenging efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…In food-packaging and polymers, during thermal treatment even at mild temperatures, such as sterilization or pasteurization, peroxide radicals , are generated that cause bond scission in polymers. This has been clearly proven to cause scission of the polyethylene backbone …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In food-packaging and polymers, during thermal treatment even at mild temperatures, such as sterilization or pasteurization, peroxide radicals , are generated that cause bond scission in polymers. This has been clearly proven to cause scission of the polyethylene backbone …”
Section: Introductionmentioning
confidence: 99%
“…This has been clearly proven to cause scission of the polyethylene backbone. 27 In natural systems, these challenges (i−iii) have been successfully addressed by (a) sequestration of the antioxidant in a matrix which can be a protein, carbohydrate or lipid, and (b) preventing undesired radical−radical couplings. 28,29 During the last 5 years, incorporation of natural antioxidants in material-matrices is exploited as advanced technology to overcome the drawbacks detailed in (i−iii).…”
Section: ■ Introductionmentioning
confidence: 99%
“…In our previous work we have clearly shown that the model oxidation relates to the onward assays which is effectively used for the determination of the kinetic parameters of both chain breaking antioxidants acting as acceptors of alkyl R and/or peroxy RO 2 radicals [1,[43][44][45][46][47][48]. To make the determination of kinetic parameters the model reaction of cumene initiated (initiator is 2,2 0 -azobisisobutyronitrile, AIBN) oxidation was designed to proceed under steady state conditions with long kinetic chains at moderate temperatures (40-80 C) where cumylhydroperoxide does not contribute additionally to the initiation of oxidation and air oxygen pressure is sufficient not to limit the process [Po 2 ¼ 20 kPa (z10 À3 mol O 2 l À1 )] [49,50].…”
Section: Theoretical Prerequisites For the Model Oxidationmentioning
confidence: 99%
“…The compounds are similar to the aromatic amines with alkyl substituents which are usually well-amenable to the kinetic analysis by means of the model oxidation [6,48,49]. The profiles of kinetic dependencies of oxygen uptake for the system cumene þ AIBN þ C 60 -AmAO-1 and C 60 -AmAO-2 are exemplified in Fig.…”
Section: Kinetic Study Of C 60 -Amao-1 and C 60 -Amao-2mentioning
confidence: 99%